Legal Protection of Thrift Trade in Indonesia - Emilia Esa Wardana; Hardian Iskandar (Dinasti Research, 2024)
The circulation of Thrift goods in Indonesia is one of the triggers for negative impacts entering Indonesia, so there is a need for regulation of the trade in Thrift goods and the need for protection for Thrift goods in Indonesia. The main problem in this writing is what the government's solution is in overcoming the problem of Thrift goods entering Indonesia. Because if left unchecked it will have a bad impact on the country. The research method used is normative research carried out with secondary data as legal material in the form of primary legal material. The results of this research show that Thrift goods are illegal goods, so the government prohibits the practice of buying and selling Thrifts as regulated in Law Number 7 of 2014 concerning trade and regulated in the Minister of Trade regulations. Apart from that, the form of protection for consumers in Thrift goods transactions is also regulated in Law number 8 of 1999 concerning consumer protection, namely that the government guarantees the health and safety of consumers, upholds justice for consumer rights, and provides legal certainty to consumers so that consumers in carrying out transactions can walk safely and comfortably.